3x + 2y = 6
2y = -3x + 6
y = -3/2x + 3
The gradient of the parallel line is -3/2
Substitute (2,10) into y = -3/2x + c and find c
10 = -3/2(2) + c
10 = -3 + c
c = 13
Therefore the equation of the line is y = -3/2x + 13
Okay, first you need to "solve" for "y".A line has equation 3x + 2y = 6. Find the equation of the line parallel to this which passes through the point (2,10)
3x + 2y = 6
2y = -3x + 6
y = -(3/2)x + 3
Now, since parallel lines have the same slope, you can set up your new equation, with the new points, using the same slope.
y - y1 = m(x - x1)
y - 10 = -3/2(x - 2
Again, solve for "y"
y - 10 = -3/2(x - 2
y - 10 = -3/2x + 3
y = -(3/2)x + 13 (<==ANSWER!!) :-)